Preparation and Evaluation of Ethyl Cellulose Coated Microcapsules of Gliclazide for Controlled Release - Chowdary, K.P.R.; Panguluri, Srinivas; Enturi, Veeraiah (Asian Journal of Chemistry, 2010)
The objective of the study is to prepare and evaluate ethyl cellulose coated microcapsules of gliclazide for controlled release. Ethyl cellulose microcapsules of gliclazide were prepared by an industrially feasible emulsification-solvent evaporation method and were evaluated for controlled release. These microcapsules were spherical, discrete, free flowing and multi-nucleate monolithic type. Microencapsulation efficiency was in the range 95-101 %. Gliclazide release from the microcapsules was slow over 24 h and depended on core:coat ratio, wall thickness and size of the microcapsules and was performed by non-fickian diffusion mechanism. Good linear relationship was observed between wall thickness of the microcapsules and release rate. Ethyl cellulose was found suitable as a microencapsulating agent for gliclazide and the ethyl cellulose microcapsules exhibited good controlled release characteristics and were found suitable for once-a-day administration of gliclazide.